SELF-EFFICACY PADA SEORANG PEREMPUAN MANTAN PECANDU NAPZA - SEBUAH STUDI KASUS - Laurike Moeliono (MANASA, 2012)
This study describes self-efficacy of a young women named Wulan (real name with permission) who was an injecting drug user. According to Bandura (1994) self-efficacy is “people's beliefs about their capabilities to produce designated levels of performance that exercise influence over events that affect their lives. Perceived self-efficacy is concerned with individuals’ beliefs in their capability to exercise control over challenging demands and their own functioning”. Self -efficacy is a very effective competence to refrain from addiction and relapse of substance abuse. Wulan has shown efficacy when she decided to refrain from her addiction, got treatment, founded the STIGMA foundation to help prevent IDU’s from stigma and discrimination , become the director of the foundation and become an active speaker at national and international conferences and seminars. To describe Wulan’s life story and struggle, the writer used qualitative research methods. Wulan’s case study was built on an in-depth interview with Wulan, listening to her testimony, secondary sources from the media, and observation. This case study has shown how self-efficacy has helped Wulan in striving for her normal life during the four phases of transition from addiction (to alcohol) to a normal life, described by Bowden (1998, in Zakrzewski & Hector, 2004) i.e. Living in the Shadow, Departure, Initiation, dan Return.